HUBUNGAN KEBIJAKAN LOKASI PRIORITAS INTERVENSI GIZI DAN PREVALENSI STUNTING DI INDONESIA - Diah Sri Wahyuni; Diahhadi Setyonaluri (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2022)
This study aims to compare the association of Indonesian’s government public health intervention in reducing the stunting prevalence. The intervention was started in 2018 in 100 districts and expanded in stages to cover 260 districts by 2020. This study adopts fixed effectmethod on regional-level 2018-2020 panel data on stunting prevalence, aggregate public health outcomes targeted under the intervention, and other regional characteristics. District’s stunting prevalence is used as a measure of the policy’s outcome while dummy of priority districts is used to measure priority effect from the interventions. The result indicates that both priority and non-priority districts experienced a declining stunting prevalence, but the reduction of prevalence in priority districts was 7.271% higher than the reduction that occurred in non-priority districts.